I Am an Old Smoking, Moving Indian Movie Star - Plaat, Henri (Netherlands; Filmmuseum, 1968)
A veiled Indian lady talks to the camera. Her story is told in images.
No dialogue
Verzio Film Festival Submission
Keywords: Experimental films